PRAYER AS A PREDICTOR OF SELF-CONFIDENCE: A Statistical Analysis - Ahmad Mohammad Tidjani; Mahfud, Ahmad; Widayatul Amalia; Zulfatul Wasilah (Jurnal Studi Islam dan Sosial, 2026)
Self-confidence is a crucial psychological factor for teachers and parents in fulfilling their educational and caregiving roles. Although prayer is generally believed to foster inner calmness and strength, empirical evidence regarding its relationship with self-confidence remains limited, particularly in the Indonesian context. This exploratory quantitative study aims to examine the relationship and statistical contribution of prayer intensity to self-confidence. Using a survey design with snowball sampling, data were collected from 30 respondents via a 1–5 Likert-scale questionnaire and analyzed using simple linear regression. The results indicate a positive but weak correlation between prayer intensity and self-confidence (R = 0.272). The coefficient of determination (R² = 0.074) indicates that prayer explains only 7.4% of the variance in self-confidence, while the remaining 92.6% is attributable to external variables. The regression coefficient of 0.181 suggests a positive direction, yet it does not reach statistical significance (p = 0.146). These findings challenge the assumption of a direct causal link between spiritual practice and psychological well-being, while affirming that prayer may serve as a preliminary predictor requiring broader validation. This study addresses a gap in the literature by providing critical preliminary empirical data for the development of large-scale research on the psychology of religion in the future.